Association between different insulin resistance surrogates and erectile dysfunction in non-diabetic men: a large population-based study - Shenghao Wu; Weiting Xia (BMC Public Health)
Abstract Background Although it is widely recognized that insulin resistance (IR) plays a critical role in the development of erectile dysfunction (ED), the specific relationship between IR and ED among non-diabetics has been little studied, and no relevant large-scale studies have been conducted. The purpose of this study is to examine the association between different IR surrogates and the risk of ED in non-diabetic populations. Methods National Health and Nutrition Examination Survey (NHANES) 2001–2004 data were used for this cross-sectional analysis. Weighted multivariable logistic regression and restricted cubic spline curves (RCS) were performed to evaluate the relationship between homeostasis model assessment (HOMA-IR), triglyceride glucose (TyG), TyG with body mass index (TyG-BMI), TyG with waist circumference (TyG-WC) and TyG with waist-to-height ratio (TyG-WHtR), and ED risk. When segmenting effects were detected, recursive algorithms were used to determine potential inflection points. Then log-likelihood ratio test and weighted segmented regression were carried out. In the sensitivity analysis, stratified and interaction analyses were performed. Results A total of 1569 (weighted: 76450963) individuals eventually were enrolled in the study. After adjusting for all confounders, the TyG did not correlate with ED (P > 0.05), whereas the other IR surrogates, HOMA-IR, TyG-BMI, TyG-WC, and TyG-WHtR, remained positively correlated with ED [ORs (95% CIs) were 1.02 (0.95, 1.10), 1.01 (1.00, 1.02), 1.00 (1.00, 1.01), 1.17 (0.84, 1.63), respectively; all P < 0.05]. Furthermore, we found the risk of ED was significantly higher when TyG-BMI > 328.94 or TyG-WC > 1128.25 or TyG-WHtR > 6.42 [the ORs (95% CIs) were 1.05 (1.02, 1.08), 1.02 (1.01, 1.03) and 51.30 (4.46, 453.64), respectively]. No interactions were found between these IR surrogates and the stratification variables. Conclusions In the non-diabetic population, ED risk was positively associated with elevated HOMA-IR, TyG-BMI, TyG-WC, and TyG-WHtR.